Factors affecting job satisfaction of public relations practitioners in major projects of the Public Investment Fund and its relationship to performance (The International Journal of Educational Sciences and Arts, 2025)
The research examines the variables which affect job satisfaction for publicity practitioners who work on principal Public Investment Fund projects (Diriyah, Neom, Giddiya, Red Sea and Rodhn). The research has used both descriptive-analytical methods to conduct their study through structured questionnaires with 54 practitioner participants. Numerous internal organizational aspects demonstrated statistical relationships with job satisfaction based on the findings of this study including organizational culture and work environment and training opportunities and administrative leadership. The investigation has verified that professionals at higher levels of job satisfaction demonstrate better professional performance results. The research points out several major factors affecting job satisfaction that emerge from inadequate upper-level leadership communication and insufficient resources and excessive workloads and restricted career advancement opportunities. Stress and burnout tend to develop when employees face these workplace factors in large-scale environments that pressure them through demanding tasks. Organizations must establish transparent work environments focused on motivation through promotion of staff participation while maintaining fair remuneration systems. The findings demonstrate an urgent need to establish both open communication systems and repetitive professional development schemes. The research results benefit both scholarly and real-world practices by providing valuable guidelines for those who should enhance employee engagement along with organizational effectiveness. The study offers important findings that future investigations in internal communication and human resource management can refer to. The study concludes that organizations should establish a strategic internal communication system to enhance both work commitment and enduring job satisfaction of their employees.
Keywords: Job Satisfaction; Public Relations Practitioners; Projects; Saudi Public Investment Fund; Quality of Job Performance